2019
DOI: 10.1038/s41598-019-50687-y
|View full text |Cite
|
Sign up to set email alerts
|

p-wave superconductivity in iron-based superconductors

Abstract: The possibility of p-wave pairing in superconductors has been proposed more than five decades ago, but has not yet been convincingly demonstrated. One difficulty is that some p-wave states are thermodynamically indistinguishable from s-wave, while others are very similar to d-wave states. Here we studied the self-field critical current of NdFeAs(O,F) thin films in order to extract absolute values of the London penetration depth, the superconducting energy gap, and the relative jump in specific heat at the supe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 55 publications
(163 reference statements)
1
29
0
Order By: Relevance
“…Deduced (0) = 740 ± 3 nm is similar to (0) = 690-850 nm measured for samples possessing maximal Tc values for cuprate counterpart La1-xSrxCuO2 [37]. By utilizing deduced (0) value the Ginzburg-Landau parameter = λ(0) (0) = 130 which is similar to La1-xSrxCuO2 [33,37] and this value is at the upper-level range for other cuprates and unconventional superconductors [15,23,24,26,[38][39][40][41][42][43]. Table I.…”
Section: Jc(sft) Analysissupporting
confidence: 74%
See 2 more Smart Citations
“…Deduced (0) = 740 ± 3 nm is similar to (0) = 690-850 nm measured for samples possessing maximal Tc values for cuprate counterpart La1-xSrxCuO2 [37]. By utilizing deduced (0) value the Ginzburg-Landau parameter = λ(0) (0) = 130 which is similar to La1-xSrxCuO2 [33,37] and this value is at the upper-level range for other cuprates and unconventional superconductors [15,23,24,26,[38][39][40][41][42][43]. Table I.…”
Section: Jc(sft) Analysissupporting
confidence: 74%
“… is the angle around the Fermi surface subtended at (, ) in the Brillouin zone (details can be found elsewhere [22,25,26]). In Eq.…”
Section: Models Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Semenok et al [44] reported the discovery of a high-temperature superconducting phase of ThH 9 at P=170 GPa which exhibits P6 3 /mmc crystallographic symmetry and superconducting transition temperature of T c =146 K. They also performed first principles calculations and deduced the effective mass in this superconductor: As we mentioned in our previous papers [12,13,46,47], first principles calculations [39,48,49] always provide α-values near 5, which is the very strong-coupling limit for s-wave symmetry (also note that other superconducting gap symmetries have weak-coupling limits of α∼5 [50][51][52]). Despite the orthodox view, several new, alternative, approaches were developed to explain NRT superconductivity in compressed hydrides: Hirsch and Marsiglio [53], Souza and Marsiglio [54], Harshman and Fiory [55], as well as Kaplan and Imry [56].…”
Section: Thh 9 (P=170 Gpa) In Uemura Plotmentioning
confidence: 81%
“…where m(T) is the is the maximum amplitude of the k-dependent d-wave gap given by Eq. 9,  is the angle around the Fermi surface subtended at (, ) in the Brillouin zone (details can be found elsewhere [58,59]). In Eq.…”
Section: Figurementioning
confidence: 99%